(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2019)
Domestic wastewater contains high concentrations of contaminants, including total coliforms and Escherichia coli indicator of fecal matter. Wastewater without treatment causes gastrointestinal diseases: amoebiasis, cholera, salmonellosis and typhoid. The objective of the study was to design a phytodepuration system using floating islands using plant substrates: Lemna minor and Salvinia auriculata. At the beginning of the bioassay, islands with the aforementioned species, the combined species and an abiotic control were placed in triplicate. The retention time was 8 days, performing microbiological analyzes at the beginning of the bioassay, on the fifth day and finally on the eighth day. A percentage of removal of E. coli was obtained, of 99.99% for Salvinia auriculata, 99.95% for Lemna minor and of 99.98% for the combined treatment. The effectiveness of removal of total coliforms in the treatments was Salvinia auriculata (99.89%), Lemna minor (99.74%) and in the combined treatment (99.84%). It is recommended to implement this technique in controlled systems to avoid eutrophication due to the rapid reproduction of these species.